Research on The Pore-Forming Mechanism of Porous Tial Intermetallics With Urea. (October 2019) - Li, Xide; Sun, Liangbo; Yang, Junsheng; Liu, Yuzuo
Abstract: Porous TiAl intermetallic compound has excellent properties, which could be applied to various fields. However, the disadvantage of current porous TiAl intermetallics is that the permeate flux is low. Urea, as an economical fertilizer with abundant sources, low price and volatile linearity, can be used as a good pore-forming agent in this paper, Urea was chosen as pore-forming agent to manufacture porous TiAl intermetallics by activation reactive sintering. After that, the effect of pore former Urea content and pore-forming mechanism were explored. The results indicated that the pore former Urea is benefit for the formation of through-holes in porous TiAl intermetallics, and the Kirkendall partial diffusion effect has great influence on the pore formation.